Ectoparasite of Rodents Collected from International Seaport, Gujarat (India) with Special Reference to Plague & Scrub Typhus - Sharma, Abhay Kumar; Kumar, Kaushal; Thomas, T G; Singh, S K (Advanced Research Publications, 2018)
Background: Rodents are well established at port areas and their arthropod ectoparasite can be vectors of many diseases. Ships play an important role in spreading disease by transporting infected vectors.Objective: In view of the seriousness of the problem the present study was undertaken to assess the prevalence of rodent–ectoparasite association at KPT, Kandla (India).Results: Four species of rodents: Tatera indica (Hardwicke), Bandicota indica (Bechstein), Rattus norvegicus (Berkenhout), Rattus rattus (Linnaeus) were trapped from the port area. Rodent Infestation rate was 84.9 per cent. Lice (46.5%) were the predominant ectoparasites retrieved from the rodents followed by mites and fleas. The rodent ectoparasite index was 13.6 per rat. A total of 32 vector larval trombiculid chigger mite (Leptotrombidium deliense, Walch) were collected from various species of rats. Chigger infestation rate was found to be 8.0 per rat. A total of 96% chigger mites were retrieved from R. norvagicus trapped from canteen area. A total 234 fleas were retrieved giving an overall flea index of 2.5 per rat. The flea species collected from rodents were Xenopsylla cheopis (Rothschild) and X. astia (Rothschild). Serological & bacteriological examination of rodent samples showed no Orentia and plague bacilli activity.Conclusion: Result of the study suggests routine surveillance for rodent and their arthropods ectoparasite to apply appropriate control measure to prevent the spreading of rodent borne diseases.